The extended theory of planned behavior in Turkish customers' intentions to visit green hotels. (18th November 2019) - Yarimoglu, Emel; Gunay, Tugrul
Abstract: Over the last decade, many studies have started to focus on understanding customers' green purchase intentions since the increasing importance of environmental issues in the hotel industry. This study examined customers' intentions to visit green hotels by using the theory of planned behavior. Two constructs, environmentally friendly activities and overall image, were incorporated into the theory, and the extended theory of planned behavior model was tested. The aim of this study was to analyze the effects of the extended theory of planned behavior constructs (attitudes towards green hotels, subjective norms, perceived control, environmentally friendly activities, and overall image) on visit intentions and also to predict the effects of visit intentions on willingness to pay, satisfaction, and loyalty. Within this aim, the research model was formed to show the antecedents and consequences of intentions to visit green hotels. Data were collected by face‐to‐face survey technique, and 400 usable questionnaires were held from the customers in Izmir City, Turkey. In the findings, four of five constructs in the antecedents of intentions, except perceived control, were found as significant, and all three consequences of intentions were found as significant. The results of the study supported the usage of the extended theory of planned behavior in the context of green hotels. Theoretical contributions and discussions were explained lastly.